MicroRNA miR-193b-3p Regulates Esophageal Cancer Progression Through Targeting RSF1 - Yao Lin; Xudong Zhao; Zhenhua Du; Zhili Jia; Siyu Zhou; Gengsheng Cao; Hengbin Wang (Cells)
Esophageal cancer (ESCA) is the sixth leading cause of cancer-related mortality worldwide. Despite the significant impact, the molecular mechanisms underlying its initiation and progression remain poorly understood. In this study, we identified mircoRNA miR-193b-3p as a critical regulator of ESCA progression and the Remodeling and Spacing Factor 1 (RSF1) as an essential target of miR-193b-3p. Analysis of the TCGA_ESCA dataset and RT-qPCR experiments revealed that RSF1 levels are significantly elevated in ESCA and inversely correlated with miR-193b-3p levels. Using a dual-luciferase reporter assay, as well as transfection of miR-193-3p mimics or inhibitors, we confirmed RSF1 as a direct target of miR-193b-3p in ESCA cells. Transfection of miR-193b-3p suppresses ESCA cell proliferation, migration, and invasion. These effects were partially reversed by exogenous RSF1 expression. Injection of AgomiR-193b-3p into mice bearing ESCA xenografts impeded tumor growth. These findings underscore the critical role of the miR-193b-3p/RSF1 axis in esophageal cancer progression.